Human immunodeficiency virus prevention and testing strategies among men who have sex with men in the UK: the PANTHEON research programme including the SELPHI RCT - Janey Sewell; Charlie Witzel; David Dunn; Fiona Lampe; Fiona Burns; Peter Weatherburn; Sheena McCormack; Leanne McCabe; Alec Miners; Valentina Cambiano; Roger Pebody; Roy Trevelion; et al. (NIHR Journals Library, 2024)
Background Rates of human immunodeficiency virus diagnoses in UnitedKingdom men who have sex with men were at a 10-year high in 2014; many recent infections indicated ongoing transmission. There was a need to increase testing rates, reduce late diagnosis and understand how to best allocate human immunodeficiency virus prevention resources. Objective We aimed to assess (1) the feasibility of human immunodeficiency virus self-testing among men who have sex with men, (2) whether the offer of free human immunodeficiency virus self-testing resulted in earlier diagnosis of human immunodeficiency virus in an online randomised controlled trial, (3) the cost-effectiveness of strategies for preventing human immunodeficiency virus in men who have sex with men, including free human immunodeficiency virus self-testing. Design We produced a systematic evidence map and conducted focus groups and interviews with men who have sex with men and relevant stakeholders to identify barriers and facilitators to human immunodeficiency virus self-testing. We conducted an internet-based randomised controlled trial (a human immunodeficiency virus Self-testing Public Health Intervention to assess whether free human immunodeficiency virus self-testingwith reminders results in earlier diagnosis of human immunodeficiency virus compared with standard of care. We evaluated the cost-effectiveness of human immunodeficiency virus prevention strategies in men who have sex with men in the UnitedKingdom using a simulation model. Data sources Databases included MEDLINE, EMBASE, Global Health, Social Policy and Practice, PsycInfo, Health Management Information Consortium, EBSCO CINAHL Plus, Cochrane Library and Web of Science. Review methods Searches combined key terms relating to human immunodeficiency virus with terms related to self-testing. Data were manually extracted through a standard form and then entered into an open-access relational map (HIVST.org). Setting Internet-based study conducted in England and Wales. Participants Participants were men (including trans men) and trans women aged ≥ 16 years old, resident in England or Wales, and not known to be human immunodeficiency virus-positive, who had ever had anal sex with a man. The qualitative work also included human immunodeficiency virus service providers and commissioners. Intervention At baseline participants were randomised (randomisation A) to the offer of a single, free baseline human immunodeficiency virus self-test versus no free human immunodeficiency virus self-test (no baseline test). At 3 months, eligible participants from the baseline test group were randomised (randomisation B) to regular offers of free human immunodeficiency virus self-testingevery 3 months for up to 24 months (regular test) versus no offer of free self-tests (no regular test). Main outcome measure The primary outcome for randomisation A was a confirmed new human immunodeficiency virus diagnosis within 3 months of randomisation (detection of prevalent infections, binary outcome). The primary outcome for randomisation B was the time from randomisation to a confirmed new human immunodeficiency virus diagnosis (detection of incident infections, time-to-event outcome). Results Focus groups (n = 47 men who have sex with men) and interviews (n = 18 key informants) showed that human immunodeficiency virus self-testing was a highly acceptable intervention for men who have sex with men, with potential to reduce barriers related to convenience, stigma and privacy. The Self-testing Public Health Intervention randomised controlled trial randomised 10,135 men whohave sex with menand trans women 3 : 2 to baseline test or no baseline test. There was no significant difference at 3 months in confirmed new human immunodeficiency virusdiagnoses [p = 0.64, 19/6049 (0.3%) in baseline test vs. 15/4062 (0.4%) in no beseline test], but human immunodeficiency virus testing rates were higher in baseline test. Following the second randomisation (n = 2308) to regular test versus no regular test there was no significant difference between groups in confirmed human immunodeficiency virus diagnoses although there was a substantial increase in testing rate in regular test versus no regular testwith no reduction in sexually transmitted infectiontesting. Modelling suggested that provision of oral tenofovir/emtricitabine pre-exposure prophylaxis increased human immunodeficiency virus testing, with anti-retroviral therapy initiation at diagnosis, and reductions in the level of condom-less sex, that each played an important role in decreasing human immunodeficiency virus incidence among men who have sex with men, and that the current human immunodeficiency virus incidence would have been double what it is if any one of them had not occurred. A combined substantial increase in human immunodeficiency virus testing and pre-exposure prophylaxis could avert 34% of infections. However, at the current cost-effectiveness threshold, a 16% reduction in the cost of delivery of testing and pre-exposure prophylaxis would be required for this scenario to offer value for money. Limitations The decline in human immunodeficiency virus incidence over the study period resulted in under-powering of the trial. However, we recruited a large number of men at risk of human immunodeficiency virus. A further limitation of the study is the low (but typical) completion rates of surveys, which may have introduced bias into the analysis of the secondary end points, although not the primary end point. Finally, the majority of the participants were white gay men, which may make our results less generalisable. Conclusions Human immunodeficiency virus self-testing is highly acceptable to men who have sex with men with potential to increase first and repeat human immunodeficiency virus testing and broaden testing options, particularly in among key sub-populations at risk of human immunodeficiency virus. The trial did not demonstrate that self-testing increased human immunodeficiency virus diagnoses linked to care, but was underpowered to do so. Future work Future research includes investigating the role of marginalisation based on ethnicity, migration status, sexual orientation and education in making testing decisions, and how social exclusion and health inequalities shape engagement with human immunodeficiency virus self-testing. Study registration This study is registered as ISRCTN20312003. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Programme Grants for Applied Research Programme (NIHR award ref: RP-PG-1212-20006) and is published in full in Programme Grants for Applied Research; Vol. 12, No. 8. See the NIHR Funding and Awards website for further award information. Plain language summary Background In 2014, new human immunodeficiency virus diagnoses among gay men in the UnitedKingdom were increasing year on year. New ways of testing for human immunodeficiency virus, such as self-testing (whereby a person can do the test themselves without a health worker there and then read the result within 15 minutes) had been developed, but it was not known whether offering self-testing would increase the number of new human immunodeficiency virus diagnoses in gay men. Methods We did an internet trial to see whether giving gay men a free human immunodeficiency virus self-testing kit would increase the number diagnosed with human immunodeficiency virus compared to not being given a free human immunodeficiency virus self-testing kit. We also looked at whether regular provision of human immunodeficiency virus self-testing kits every 3 months over a 2-year period would allow a more prompt diagnosis among those who got a new human immunodeficiency virus infection. Finally, we looked at value for money of providing free human immunodeficiency virus self-testing and other interventions including pre-exposure prophylaxis and early human immunodeficiency virus treatment (at the point of diagnosis), to prevent human immunodeficiency virus infection. Results The ease and privacy of human immunodeficiency virus self-testing meant that it was an acceptable way of testing for men who have sex with men.